Ultrafine cobalt nanoparticles supported on carbon nanospheres for hydrolysis of sodium borohydride. (December 2020) - Zhang, Hongming; Xu, Guochang; Zhang, Lu; Wang, Wenfeng; Miao, Wenkang; Chen, Kangli; Cheng, Lina; Li, Yuan; Han, Shumin
Abstract: Sodium borohydride (NaBH4 ) is an ideal chemical carrier of hydrogen due to its high hydrogen release capacity via hydrolysis, however the reaction is restricted by a competent catalyst. Herein, we present an efficient catalyst – ultrafine non-noble Co nanoparticles supported on carbon nanospheres (CNSs) (CNSs@Co), for hydrogen generation from NaBH4 hydrolysis in alkaline media. The ultrafine Co nanoparticles distribute evenly over the surface of the CNSs by adjusting solubility of a by-product – NaBO2 within ethanol. The as-prepared CNSs@Co catalyst has a glorious catalytic activity for hydrogen evolution of NaBH4 . It shows a high hydrogen generation rate (HGR) of 7447 mL H 2 . min − 1 ⋅ g M − 1 at 30 °C, and a low activation energy of 40.79 kJ mol −1 . Besides, the catalyst exhibits a stable cycling capability in a consecutive cycling test. The outstanding catalytic performance of the CNSs@Co catalyst could attribute to the ultrafine size of the Co nanoparticles (∼7 nm) and its uniform dispersion supported by the CNSs. We believe the catalyst together with its synthetic method will provide a probable strategy to promote the hydrogen generation from NaBH4 . Graphical abstract: Image 1 Highlights: Ultrafine Co nanoparticles ∼7 nm are loaded on CNSs carriers for NaBH4 hydrolysis. Mixed solvent affected the Co size of by adjusting solubility of by-product NaBO2 . Hydrolysis of NaBH4 with CNSs@Co reveals high HGR of 7447 mLH2 ·min −1 · gM −1 . CNSs@Co catalyst exhibits good reusability for NaBH4 hydrolysis.